Metsovo Lung: History of Population Environmental Exposure to Asbestos - Sxiza, C.; Zagorianakou, N.; Vlami, C.; Farantos, G.; Rapisarda, V.; Dounias, G. (European Scientific Journal, ESJ, 2025)
Objectives: Our aim is to review all the literature concerning Metsovo Lung as an emblematic story that demonstrates the strong relationship between non-occupational but environmental and ecological exposure to asbestos and lung diseases. Materials and Methods: We searched data from the 1970s when extensive pleural calcifications causing malignant mesothelioma appeared at a high incidence beyond expectation. The most reliable studies were selected for our research from 2017-2023. Results: There wasn’t occupational exposure in Epirus. This finding reasonably raised the question of whether it was indeed tuberculous pleurisy or something else. The biopsies carried out confirmed that these were tremolite asbestos fibers. These fibers were derived from ‘luto’, a water-shielding material containing asbestos. The entire population of Metsovo was exposed to asbestos, without knowing it. This is a global phenomenon, according to which, it is made from a traditional shielding material. The abandonment of ‘luto’ and its non-use brought about a gradual reduction of the phenomenon, which also marks the reduction of mesothelioma. Conclusion: Lessons learned from the history of Metsovo lung showed the importance of the combination of theory and practice in the context of nonoccupational exposure to asbestos. From a public health point of view, it’s crucial to know whether exposure to low levels of asbestos is able to induce pleural mesothelioma.